Candida albicans susceptibility to lactoperoxidase-generated hypoiodite - Mohamed Ahariz; Philippe Courtois (Dove Medical Press, 2010)
Mohamed Ahariz1, Philippe Courtois21Laboratory of Experimental Hormonology, Université Libre de Bruxelles, Brussels, Belgium; 2Laboratory of Experimental Hormonology, Université Libre de Bruxelles, Brussels, Belgium and UER de Biologie Médicale, Haute Ecole Francisco Ferrer, Brussels, BelgiumAbstract: In vivo, lactoperoxidase produces hypothiocyanite (OSCN-) from thiocyanate (SCN-) in the presence of hydrogen peroxide (H2O2); in vitro, iodide (I-) can be oxidized into hypoiodite (OI-) by this enzyme. The aim of this study was to compare in vitro the anti-Candida effect of iodide versus thiocyanate used as lactoperoxidase substrate to prevent Candida biofilms development. Candida albicans ATCC 10231 susceptibility upon both peroxidase systems was tested in three different experimental designs: (i) in a liquid culture medium, (ii) in an interface model between solid culture medium and gel containing the enzymic systems, (iii) in a biofilm model onto titanium and acrylic resin. Yeast growth in liquid medium was monitored by turbidimetry at 600 nm. Material-adherent yeast biomass was evaluated by the tetrazolium salt MTT method. The iodide-peroxidase system has been shown to inhibit Candida biofilm formation at lower substrate concentrations (~200 fold less H2O2 donor) and for longer incubation periods than the thiocyanate-peroxidase system. In conclusion, efficiency of lactoperoxidase-generated OI- to prevent C. albicans biofilm development allows refining iodine antifungal use in ex vivo conditions.Keywords: denture, iodide, oral, peroxidase, saliva, titanium